Handbook of antioxidants - Wypych, George (ChemTec Publishing, 2020)
"Handbook of Antioxidants contains information on both natural and man-made antioxidants available in natural products and added in numerous industrial applications. The book contains 10 chapters, each discussing different aspect of phenomena occurring when materials are exposed to ambient air which contains oxygen, ozone, singlet oxygen, and many other oxidizing species (radicals). The introduction includes discussion of general concepts related to antioxidants and their application. This is followed in Chapter 2 by information on existing natural and synthetic antioxidants which are presented in form of tables characterizing their general properties and applications. Chapter 3 contains a discussion of formation and action of oxidizing species in living organisms, ambient air, industrial environment, and chemical reactions. Essential aspects of physics and chemistry related to the oxidizing species are discussed here. Chapter 4 is devoted to the theories and mechanisms of stabilization according to which antioxidants perform in various environments. Suggestions are made on typical conditions of performance and potential use in different fields of application. Stability of antioxidants and its performance indicators, important for predicting the lifetime of antioxidant protection are discussed in Chapter 5. Different reasons for instability are pointed out in the evaluation. Principles of antioxidants selection are given in Chapter 6, including the influence of stabilizer properties and expectations from the final products. Chapters 7 and 8 give specific information on degradation and stabilization of different polymers & rubbers and final products manufactured from them, respectively. The subjects discussed in each case of polymer or group of products are given in Table of Contents. Specific effects of antioxidants on other components of formulation in Chapter 9. Analytical methods, which are most frequently used in oxidation and its prevention, are discussed in Chapter 10 to show their potential in further understanding of the subject. This book is an excellent companion to the Databook of Antioxidants which has also been published recently. Both books supplement each other without repeating the same information--one contains data another theory, mechanisms of action, practical effects and implications of application"-- Provided by publisher.
Keywords: Antioxidants -- Handbooks, manuals, etc.; elektronické knihy; electronic books